Uma abordagem sobre a inevitabilidade dos conflitos no período entre guerras - Alexandre Rocha Violante (Navigator)
In this article, it was attempted to discuss how the League of Nations, an international forum created after the First World War, could interfere that conflicts could be avoided in a more general and global scale. So, it was tried to prove as the main objective of this article that in the interwar period, despite the attempt of great change in the international order, which occurred in said Utopian principles, avoid them, was virtually impossible. As secondary objectives, this article aims to analyze politically: a) the changes in international relations after the First World War; b) the League of Nations, which sought to change the security mechanism used to prevent and resolve conflicts; and c) the systematic of the new collective security mechanism of the League, particularly the constraints to which it was submitted. Thus, based on qualitative theories of international relations at that time and in contemporary, it was found the failure of the League of Nations, along the lines of time, and their collective security mechanism aimed at the implementation of a new structured world order multilaterally, in the multipolar and democratic principles of global governance.